Role of AICTE-IDEA Lab in Experiential Learning and Acquisition of Multidisciplinary Skills for Execution of Undergraduate Projects - Katageri, Basavaraj G.; Gadagi, Amith H.; Tigadi, Arun S.; Raikar, Rajkumar V. (Journal of Engineering Education Transformations, 2025)
This article emphasizes on the importance of skill- based training and multidisciplinary approach in the technical education. To ascertain the effectiveness of such concepts, the activities and projects carried out in IDEA (Idea, Development, Evaluation and Application) Lab established under AICTE-IDEA Lab Scheme are focused and discussed in this paper. After undergoing an experiential hands-on training on the machines and software’s available, as the resources of IDEA Lab, eight interdisciplinary and multidisciplinary engineering projects were completed by the students under the facilitation of faculties called Technical Gurus. The methodology involved in carrying out two such projects are discussed in detail whilst the other projects are listed. From the accomplished projects, it is observed that the training imparted in IDEA Lab and the experiential learning certainly enhanced the acquisition of multidisciplinary skills in the students, which are essential in converting the Ideas into Prototypes.